On the investigations of Nikola Obreshkoff connected with the regularly monotonic functions (in Bulgarian, summary in English) - Genchev, Todor (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 1997)
A short survey of some investigations of the academician N. Obreshkoff connected with the regularly monotonic functions introduced by S. N. Bernstein is proposed.